SMEs in Argentina: Who are the exporters - Gianmarco I. P. Ottaviano; Christian Volpe Martincus (Fondazione Eni Enrico Mattei (FEEM), 2009)
There exists a growing body of literature which looks at export decisions made by firms. Most studies focus on developed countries and do not explore whether different behavioral patterns prevail over the firm size distribution. This paper aims at filling this gap in the literature by analyzing the export behavior of a statistically representative sample of 192 Small and Medium-Size Enterprises (SMEs) in a developing country, Argentina, over the period 1996-1998. We find that the level of employment, sourcing from abroad, investment in product improvement and average productivity are associated with a higher probability of exporting. Training activities for employees are important to export outside of MERCOSUR.
Keywords: F10; F14; D21; L60; 330; SME; Exports; Argentina